2008
DOI: 10.1016/j.juro.2007.11.078
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Aggressiveness of Prostatic Carcinomas Related to RNASEL R462Q Allelic Variants

Abstract: Purpose-Allelic variations in the HPC1/RNASEL gene, especially the R462Q single nucleotide polymorphism, have been associated with increased susceptibility to prostate cancer. Prior studies have suggested that HPC1-or R462Q-associated tumors present with more aggressive clinical features. We assessed a series of men undergoing radical prostatectomy for clinical and pathological measures of tumor aggressiveness according to the RNASEL R462Q genotype.Methods-A prospective analysis of 232 men treated for prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Initially, Casey et al, (2002) showed that the R462Q variant resulted in a significant decrease in RNASEL enzymatic activity and that the variant was significantly associated with an increasing risk of prostate cancer in a case control cohort. Several subsequent studies have been reported, which suggest that RNASEL common variants are associated with risk of familial prostate cancer (17,35,36); however these findings are not universally replicable (3741). Results of a meta-analysis of ten independent RNASEL genotyping studies for the variants E265X, R462Q, and D541E suggested that although there was no overall effect on prostate cancer risk, there was an ethnic associated increase in risk of prostate cancer (<2.0) with the D541E variant in Caucasians regardless of family history (42).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, Casey et al, (2002) showed that the R462Q variant resulted in a significant decrease in RNASEL enzymatic activity and that the variant was significantly associated with an increasing risk of prostate cancer in a case control cohort. Several subsequent studies have been reported, which suggest that RNASEL common variants are associated with risk of familial prostate cancer (17,35,36); however these findings are not universally replicable (3741). Results of a meta-analysis of ten independent RNASEL genotyping studies for the variants E265X, R462Q, and D541E suggested that although there was no overall effect on prostate cancer risk, there was an ethnic associated increase in risk of prostate cancer (<2.0) with the D541E variant in Caucasians regardless of family history (42).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] While the clinical implications of common genetic variants associated with PCa risk remain unclear, [28][29][30][31][32][33][34] deleterious germline mutations in both genes, BRCA1 and BRCA2, have been associated with more aggressive disease and poor clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…2224 These studies have either found no association, examined SNPs no longer considered PC-risk specific alleles or examined different SNPs from those in this analysis. To our knowledge, the present study is the first to include such a large number of PC-risk SNPs and their association to tumor volume and prostate size.…”
Section: Discussionmentioning
confidence: 96%